2023
DOI: 10.1111/cas.15903
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐expressing oncolytic adenovirus + chemoradiation inhibited pancreatic cancer growth in a hamster model

Abstract: Past clinical trials of adjuvant therapy combined with interferon (IFN) alpha, fluorouracil, cisplatin, and radiation improved the 5‐year survival rate of pancreatic ductal adenocarcinoma (PDAC). However, these trials also revealed the disadvantages of the systemic toxicity of IFN and insufficient delivery of IFN. To improve efficacy and tolerability, we have developed an oncolytic adenovirus‐expressing IFN (IFN‐OAd). Here, we evaluated IFN‐OAd in combination with chemotherapy (gemcitabine + nab‐paclitaxel) + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Expression of IFN in OVs can effectively induce tumor cell death through modulation of various pathways ( 22 ). Studies have demonstrated that oncolytic adenovirus (OAd) expressing IFN (IFN-OAd) significantly suppresses tumor growth in hamster pancreatic cancer models, leading to increased infiltration of tumor-infiltrating lymphocytes (TILs) ( 23 ). Furthermore, the incorporation of CD47 and IFNγ genes into MYXV results in the production of MYXV_IFNγ and MYXV_CD47, respectively.…”
Section: Engineering Modification Of Ovsmentioning
confidence: 99%
“…Expression of IFN in OVs can effectively induce tumor cell death through modulation of various pathways ( 22 ). Studies have demonstrated that oncolytic adenovirus (OAd) expressing IFN (IFN-OAd) significantly suppresses tumor growth in hamster pancreatic cancer models, leading to increased infiltration of tumor-infiltrating lymphocytes (TILs) ( 23 ). Furthermore, the incorporation of CD47 and IFNγ genes into MYXV results in the production of MYXV_IFNγ and MYXV_CD47, respectively.…”
Section: Engineering Modification Of Ovsmentioning
confidence: 99%